2021
DOI: 10.3390/ma14154230
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for the Detection of SARS-CoV-2 Based on Graphene-Impedimetric Immunosensor

Abstract: Due to the SARS-CoV-2 pandemic, there has been an increase in the search for affordable healthcare devices for mass testing and rapid diagnosis. In this context, this work described a new methodology for SARS-CoV-2 detection based on an impedimetric immunosensor developed using the advantageous immobilization of antibodies in the reduced graphene oxide (rGO). The rGO was obtained by chemical synthesis from the commercial graphene oxide (GO), and the materials were morphologically, electrochemically and visuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 32 publications
0
19
2
Order By: Relevance
“…Previous reports have found that Electrochemical Impedance Spectroscopy (EIS)-based biosensors rapidly detect bioreceptors associated with SARS-CoV-2 infection, with high sensitivity, specificity and reliability [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. In such biosensors, bioreceptors are anchored on the working electrode surface to directly bind to target molecules specifically, generating changes in the interfacial properties in a concentration-dependent manner [ [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have found that Electrochemical Impedance Spectroscopy (EIS)-based biosensors rapidly detect bioreceptors associated with SARS-CoV-2 infection, with high sensitivity, specificity and reliability [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. In such biosensors, bioreceptors are anchored on the working electrode surface to directly bind to target molecules specifically, generating changes in the interfacial properties in a concentration-dependent manner [ [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past three years, several electrochemical biosensors have been developed for detecting SARS-CoV-2 antigens based on diverse modified electrodes [25] , [26] , [27] , [28] , [29] . Despite such successes, the majority of these strategies either require sophisticated fabrication of an electrochemically responsive interface or synthesis of electroactive labels that link to bioreceptors [30] , [31] , or suffer from potential cross-reactivity of SARS-CoV-2 antibodies with antibodies generated against other coronaviruses due to their high genome similarities [32] , [33] , [34] , [35] . These drawbacks thereby result in potential tradeoffs in terms of sensitivity, specificity and user-friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zaccariotto et al [ 97 ], an impedimetric immunosensor was developed by immobilizing antibodies on modified glassy carbon for SARS-CoV-2 detection. Figure 4 illustrates the fabrication steps of the electrochemical immunosensor.…”
Section: Sars-cov-2 Electrochemical Biosensorsmentioning
confidence: 99%